The Future of Observability with OpenTelemetry - Young, Ted (O'Reilly Media, Inc., 2021)
The world of observability is in the midst of a seismic shift. Until recently, collecting telemetry data meant running multiple, uncoordinated pipelines. Now, OpenTelemetry provides users with a single integrated stream of data, containing all common forms of observability. With this report, CTOs, analysts, system architects, and DevOps practitioners will learn how OpenTelemetry will change the way we practice observability. Author Ted Young, cofounder of the OpenTelemetry project, demonstrates how this collection of tools, APIs, and SDKs gives OSS libraries and services the ability to provide their own instrumentation. You'll save time, often in situations where time is critical, by focusing on how your system is changing without first having to identify what is changing. By the end of this report, you'll learn how a modern observability pipeline works. You'll examine: How the field of observability will change over the next two years Why native instrumentation for OSS libraries is a revolutionary idea How some current practices are very cumbersome wastes of time The promises of AIOps: which ones are valid, and which are hype How to budget for and capitalize on the upcoming shifts in technology The quality of different vendor and technology offerings.
Online resource; Title from title page (viewed December 25, 2021)
Keywords: Application software -- Development -- Computer programs; Application program interfaces (Computer software); Cloud computing; Logiciels d'application; Développement; Logiciels; Interfaces de programmation d'applications; Infonuagique; APIs (interfaces); Application software; Development; Computer programs